Femtosecond laser micro-machining - Wee, Jonas Chee Yong (Nanyang Technological University, 2024)
Femtosecond laser micro-machining is a precise and advanced laser technique. It can emit ultrashort laser pulse in the femtosecond range (10-15 seconds) with intense high peak power, allowing precise material removal. This technique minimizes thermal damage to the surrounding material while maintaining structural integrity, offering extreme precision and accuracy. This property makes the Femtosecond laser micro-machining suitable to be used on a wide range of materials opening possibilities for various applications. Femtosecond laser micro-machining is a cutting-edge technology that brought significant advancement to the micro-fabrication of optical fibers.